Pneumocystis pneumonia in COVID-19 patients: A comprehensive review. Issue 2 (February 2023) - Sasani, Elahe; Bahrami, Fares; Salehi, Mohammadreza; Aala, Farzad; Bakhtiari, Ronak; Abdollahi, Alireza; Bashardoust, Bahareh; Abdorahimi, Mahsa; Khodavaisy, Sadegh
Abstract: The admitted patients of intensive care units with coronavirus disease 2019 (COVID-19) meet the challenges of subsequent infections. Opportunistic fungal infections such as Pneumocystis pneumonia (PCP) are among the important factors in the context of COVID-19 patients affecting illness severity and mortality. We reviewed the literature on COVID-19 patients with PCP to identify features of this infection. Although studies confirmed at least the presence of one immunosuppressive condition in half of PCP patients, this disease can also occur in immunocompetent patients who developed the immunosuppressive condition during Covid-19 treatment. The major risk factors associated with COVID-19 patients with PCP can be considered low lymphocyte counts and corticosteroid therapy. Diagnostic and treatment options are complicated by the overlapping clinical and radiologic characteristics of PCP and COVID-19 pneumonia. Therefore, physicians should comprehensively evaluate high-risk patients for PCP prophylaxis.